The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4236/ns.2013.511139
|View full text |Cite
|
Sign up to set email alerts
|

Can the early bird catch the worm? Effects of early rising on leukocyte subsets via modification of autonomic nervous system and the effect on glucose levels

Abstract: The importance of sleep has been described in proverbs such as "the early bird catches the worm". However, there are few scientific reports on the effects of early rising. Therefore, early risers (Group E) and late risers (Group L) were compared and the number and ratio of leukocytes, body temperature, glucose and its associated hormones were studied. Furthermore, each group was divided into two groups by the duration of sleep and the following four groups were compared: early risers with short sleep (Group E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This balance is easily altered by small changes in our health. For example, the duration of sleep can affect this balance [8] [9]. Furthermore, long-lasting stress induces unbalanced internal conditions that might The AT group showed Yin+ (dark blue); however, it did not have Yang+ (vivid red).…”
Section: The At Group Showed More Sympathetic Nerve Dominance Than Thmentioning
confidence: 99%
“…This balance is easily altered by small changes in our health. For example, the duration of sleep can affect this balance [8] [9]. Furthermore, long-lasting stress induces unbalanced internal conditions that might The AT group showed Yin+ (dark blue); however, it did not have Yang+ (vivid red).…”
Section: The At Group Showed More Sympathetic Nerve Dominance Than Thmentioning
confidence: 99%
“…Living in tune with the nature's rhythms and cycles is highly recommended by both spirituality and science� It is reflected in many cultures' practices of rising early (Kumaran, Raghavendra and Manjunath 2012; Hynes 1887)� Over generations, it has been a convention for Muslims to get up early in the morning in general and at dawn in particular� The Holy Qur'an (610 C�E�), emphasizes the importance of maintaining a pattern of light and darkness and describes dawn as a fixed time early in the morning (about one and a half hours before sunrise), which is the sacred time to rise� Hence, rising at dawn individuals are prescribed to engage in doing prayer including being thankful and asking for forgiveness (Q� 51:17 -18)� It has also been a prescribed discipline of TPM� This medical doctrine discourages sleeping during astronomical twilight as the time for rising (based on the Qur'an (al -Ṭabarī 2002: 397)) in order to prevent certain disorders to happen (ʿAqīlī 2006: 2: 92;Jurjānī 2006: 3:477)� The descriptions from the Qur'an and TPM seem to be scientific� It has been observed that people who get up earlier in the morning adapt better to circadian rhythm� Balance of circadian rhythm can also boost the secretion of hormones in the body by improving endocrine and metabolic functions (Reiter, Rosales -Corral and Sharma 2020)� According to an earlier study, compared with late risers, early risers showed higher ratio of lymphocytes and a lower numbers and ratio of granulocytes showing parasympathetic nerve dominance� Early risers showed higher levels of glucose and its related hormones than late risers, indicating sympathetic nerve dominance (Watanabe et al� 2013)� The bases behind rising early in the morning can be believed to influence an individual's performance during the day� Previous researches have shown that timing of wakefulness correlated closely with academic performance� Compared to those with the lowest academic performance, students with the highest performance had significantly earlier wake times (Eliasson, Lettieri and Eliasson 2010)� Early morning awakening is acknowledged in compiled datas to improve significantly the performance related to verbal and spatial memory task requiring attention and concentration such as selective attention, phasic alertness, and vigilance including concentration and sustained attention (Kumaran, Raghavendra and Manjunath 2012)�…”
Section: Introductionmentioning
confidence: 99%